2016
DOI: 10.3892/etm.2016.3166
|View full text |Cite
|
Sign up to set email alerts
|

Subtraction CT angiography for the detection of intracranial aneurysms: A meta-analysis

Abstract: Abstract. The aim of this meta-analysis was to investigate the accuracy of subtraction computed tomography angiography (CTA) for diagnosing intracranial aneurysms. A systematic literature search up to January 1, 2013 was performed in PubMed. Two independent reviewers selected 8 studies that compared subtraction CTA with digital subtraction angiography. Data from the studies were used to construct a 2x2 contingency table on a per-patient basis in ≥5 diseased and 5 non-diseased patients, with additional data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Prior clinical evaluations that compared CTA or MRA with DSA revealed that the diagnostic value of CTA or MRA approaches that of DSA. A recent investigation [ 13 ] pooled 8 studies to explore the accuracy of subtraction CTA compared with DSA for diagnosing intracranial aneurysm; the pooled sensitivity and specificity were 96% and 91%, respectively. In addition, the author also suggested that CTA is a highly sensitive, specific and noninvasive imaging method to diagnose intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…Prior clinical evaluations that compared CTA or MRA with DSA revealed that the diagnostic value of CTA or MRA approaches that of DSA. A recent investigation [ 13 ] pooled 8 studies to explore the accuracy of subtraction CTA compared with DSA for diagnosing intracranial aneurysm; the pooled sensitivity and specificity were 96% and 91%, respectively. In addition, the author also suggested that CTA is a highly sensitive, specific and noninvasive imaging method to diagnose intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…This is partially addressed by mask subtraction CT angiography that subtracts noncontrast CT from CT angiography, although this can suffer from misregistration artifacts from movement between temporally separate scans. 51…”
Section: Cerebrovascularmentioning
confidence: 99%
“…This is partially addressed by mask subtraction CT angiography that subtracts noncontrast CT from CT angiography, although this can suffer from misregistration artifacts from movement between temporally separate scans. 51 Bone-subtraction DECT angiography has lower radiation dose than mask subtraction CT angiography without motion misregistration artifacts. When compared to threedimensional rotational digital subtraction angiography for aneurysm detection, bone-subtraction CT angiography was found to have high accuracy, with findings closely correlating with aneurysm size measurements.…”
Section: Aneurysm and Stenosis Assessmentmentioning
confidence: 99%
“…In addition, DE-CTA from various vendors now offers skull subtraction based on the material-specific properties of bone, facilitating 3D reconstruction of the intracranial vasculature and improved visualization of aneurysms at the skull base. Feng et al 21 recently showed that DE-CTA yielded a sensitivity and specificity of 95% and 100%, respectively, with a 60% reduction in average radiation exposure compared to DSA.…”
Section: Ctamentioning
confidence: 99%